Single-cell RNA sequencing of equine mesenchymal stromal cells from primary donor-matched tissue sources reveals functional heterogeneity in immune modulation and cell motility - Harman, Rebecca M. (Stem Cell Res Ther, 2020)
BACKGROUND: The efficacy of mesenchymal stromal cell (MSC) therapy is thought to depend on the intrinsic heterogeneity of MSC cultures isolated from different tissue sources as well as individual MSCs isolated from the same tissue source, neither of which is well understood. To study this, we used MSC cultures isolated from horses. The horse is recognized as a physiologically relevant large animal model appropriate for translational MSC studies. Moreover, due to its large size the horse allows for the simultaneous collection of adequate samples from multiple tissues of the same animal, and thus, for the unique collection of donor matched MSC cultures from different sources. The latter is much more challenging in mice and humans due to body size and ethical constraints, respectively. METHODS: In the present study, we performed single-cell RNA sequencing (scRNA-seq) on primary equine MSCs that were collected from three donor-matched tissue sources; adipose tissue (AT), bone marrow (BM), and peripheral blood (PB). Based on transcriptional differences detected with scRNA-seq, we performed functional experiments to examine motility and immune regulatory function in distinct MSC populations. RESULTS: We observed both inter- and intra-source heterogeneity across the three sources of equine MSCs. Functional experiments demonstrated that transcriptional differences correspond with phenotypic variance in cellular motility and immune regulatory function. Specifically, we found that (i) differential expression of junctional adhesion molecule 2 (JAM2) between MSC cultures from the three donor-matched tissue sources translated into altered cell motility of BM-derived MSCs when RNA interference was used to knock down this gene, and (ii) differences in C-X-C motif chemokine ligand 6 (CXCL6) expression in clonal MSC lines derived from the same tissue source correlated with the chemoattractive capacity of PB-derived MSCs. CONCLUSIONS: Ultimately, these findings will enhance our understanding of MSC heterogeneity and will lead to improvements in the therapeutic potential of MSCs, accelerating the transition from bench to bedside. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13287-020-02043-5.